Chlorophyll and phenolic contents in Albizia chinensis (Os beck) Merrill population collected from Western Himalaya - Singh, Chatar; Todaria, N.P. (Indian Journal of Agroforestry, 2020)
Chlorophyll variation in thirteen populations of Albizia chinensis collected from Garhwal, Kumaon hills and Himachal Pradesh in Western Himalaya and grown under similar environmental condition at Srinagar-Garhwal (550 m altitude) was studied. The results did not indicate clear-cut pattern with regards to various geographical variables. On average middle altitudes populations (960-1070 m) were having higher chlorophyll a, b content as well higher chlorophyll a+b. This may be an indication of best adaptation range ofthis species. Statistically significant (p=0.01) correlations were observed between latitude and chlorophyll a+b but significantly (p=0.05) negative correlation was recorded between latitude and chlorophyll a/b.